Generation and in vitro characterisation of inhibitory nanobodies towards plasminogen activator inhibitor 1 - Zhou, Xiaohua; Hendrickx, Maarten L. V.; Hassanzadeh-Ghassabeh, Gholamreza; Muyldermans, Serge; Declerck, Paul J. (Thrombosis and Haemostasis, 2016)
Plasminogen activator inhibitor 1 (PAI-1) is the principal physiological inhibitor of tissue-type plasminogen activator (t-PA) and has been identified as a risk factor in cardiovascular diseases. In order to generate nanobodies against PAI-1 to interfere with its functional properties, we constructed three nanobody libraries upon immunisation of three alpacas with three different PAI-1 variants. Three panels of nanobodies were selected against these PAI-1 variants. Evaluation of the amino acid sequence identity of the complementarity determining region-3 (CDR3) reveals 34 clusters in total. Five nanobodies (VHH-s-a98, VHH-2w-64, VHH-s-a27, VHH-s-a93 and VHH-2g-42) representing five clusters exhibit inhibition towards PAI-1 activity. VHH-s-a98 and VHH-2w-64 inhibit both glycosylated and non-glycosylated PAI-1 variants through a substrate-inducing mechanism, and bind to two different regions close to αhC and the hinge region of αhF; the profibrinolytic effect of both nanobodies was confirmed using an in vitro clot lysis assay. VHH-s-a93 may inhibit PAI-1 activity by preventing the formation of the initial PAI-1•t-PA complex formation and binds to the hinge region of the reactive centre loop. Epitopes of VHH-s-a27 and VHH-2g-42 could not be deduced yet. These five nanobodies interfere with PAI-1 activity through different mechanisms and merit further evaluation for the development of future profibrinolytic therapeutics.
Keywords: Cardiovascular diseases; fibrinolysis; nanobodies; neutralising antibody fragments; plasminogen activator inhibitor 1